Hard-Disk Drives: The Good, the Bad, and the Ugly. - ELERATH, JON (Communications of the ACM, 2009)
The article discusses computer hard-disk drive (HDD) reliability, examining and describing new HDD technologies and increased capacities that create new categories of failure modes. HDD reliability has been the significant factor in data storage, the author states. Other topics include the use of redundant array of independent disks (RAID) to address needs for redundancy at systems levels, the use of two redundant disks, or dual parity, to increase storage system reliability, and the production of one-terabyte HDDs.